Advancing Medication Reconciliation in an Outpatient Internal Medicine Clinic through a Pharmacist-Led Educational Initiative - Sarah M. Westberg, Pharm.D.; Kathrine Beeksma, R.N. (INNOVATIONS in Pharmacy, 2010)
Objectives: To develop and deliver an effective pharmacist-led educational initiative to clinic staff to advance medication reconciliation in the electronic medical record of an outpatient internal medicine clinic.Methods: An educational initiative designed to improve the ability of nursing staff in medication reconciliation was launched in the outpatient internal medicine clinic of a regional healthcare system. The education was provided by the pharmacist to clinic nursing staff, including registered nurses, licensed practical nurses, and certified medical assistants. The impact of this training was measured through pre-initiation and post-implementation surveys, competency assessments and an audit. Results: The educational initiative was successfully designed and delivered to clinic nursing staff. Assessment of the initiative found that all nursing staff completing competency assessments successfully passed. Pre-initiation- and post-implementation- survey responses on the self-assessed ability to gather and document accurate medication lists did not show significant changes. Informal observations in the clinic indicated that this initiative changed the culture of the clinic, creating increased awareness of the importance of accurate medications and increased emphasis on medication reconciliation.Conclusions: The expertise of pharmacists can be utilized to educate nursing staff on the skills and abilities necessary to gather and document accurate medication lists. This study did not find measurable changes in the accuracy of medication lists in this clinic. Future research is needed to determine the best methods to train health professionals in medication reconciliation to ensure accurate medication lists in the outpatient setting.